Quantity, Quality and Originality: The Effects of Incentives on Creativity - Katharina Laske; Marina Schröder (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We introduce a novel experimental design in which creativity is incentivized and measured along three dimensions: quantity, quality and originality of ideas. We implement piece rate incentives for quantity alone, quantity in combination with quality and quantity in combination with originality and compare the results to a baseline with a fixed wage. Studying the effect of incentives on performance in the separate dimensions of creativity, we find that incentives significantly affect the quantity and average quality of ideas, but not the average originality. We show that incentives have both positive direct and negative spillover effects on performance in these dimensions and that organizations, therefore, face tradeoffs when introducing incentives for creative performance. When investigating the effect of incentives on a combined measure of innovation, i.e., the number of creative ideas that are at the same time of high quality and original, we find that incentives for both quantity and originality perform best.
Keywords: C91; J33; M52; O30; 330; creativity; multitasking; laboratory experiment; real-effort; incentives